A dielectric anomaly observed for doubly reduced mixed-valence polyoxometalate. Issue 51 (2nd June 2017) - Nakamura, Ippei; Tsunashima, Ryo; Nishihara, Sadafumi; Inoue, Katsuya; Akutagawa, Tomoyuki
Abstract : A doubly reduced mixed-valence Keggin cluster exhibited a dielectric anomaly that originated from dipole relaxation. Abstract : Benzimidazolium is revealed to form quasi-isostructural crystals of mixed-valence molecular metal oxides that consist of [PMoV2MoVI10O40 ] 5− and fully oxidized [BWVI12O40 ] 5− . The structure and dielectric behaviour were compared and a dielectric anomaly was evident due to the electric dipole relaxation in the mixed-valence system.